Variability of ENSO forecast skill in 2-year global reforecasts over the 20th Century - Weisheimer, A; Balmaseda, M; Stockdale, T; Sharmila, S; Mayer, M; Hendon, H; Alves, O (American Geophysical Union, 2022)
In order to explore temporal changes of predictability of ENSO, a novel set of global biennial climate reforecasts for the historical period 1901 – 2010 has been generated using a modern initialized coupled forecasting system. We find distinct periods of enhanced long-range skill at the beginning and end of the 20th century and an extended multi37 decadal epoch of reduced skill during the 1930s-1950s. Once the forecast skill extends beyond the first spring barrier, the predictability limit is much enhanced and our results provide support for the feasibility of skilful ENSO forecasts up to 18 months. Changes in the mean state, variability (amplitude), persistence, seasonal cycle and predictability suggest that multi-decadal variations in the dynamical characteristics of ENSO rather than the data coverage and quality of the observations have primarily driven the reported non43 monotonic skill modulations.